REINFORCING AGENCY FROM ENTERTAINMENT INDUSTRY IMPRESSION MANAGEMENT: SEMIOTIC ANALYSIS OF DOJA CAT'S "ATTENTION" MUSIC VIDEO - Liora, Jeu Lael; Halimi, Sisilia Setiawati (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2024)
Celebrities in the entertainment industry frequently engage in impression management, a practice driven by the commodification of their personas. This study explores Doja Cat’s music video Attention, examining how she balances impression management with expressions of personal agency as a celebrity. Employing Roland Barthes’ semiotic analysis and Erving Goffman’s impression management theory, the study analyzes the visual signs embedded in the music video. The findings reveal that Doja Cat strategically performs impression management to align with stakeholder expectations, ensuring her continued marketability and perceived value within the entertainment industry. However, she also challenges these expectations by introducing symbols of agency, asserting her individuality and creative autonomy. This dual approach reflects the complexities of navigating societal pressures and personal expression in celebrity culture. Future studies could extend this analysis by examining Attention through a gender studies lens, focusing on themes such as female objectification and exploitation within the broader context of celebrity culture and the entertainment industry.